Optimization, Validation, and Application of Cleanup-Coupled Liquid Chromatography–Tandem Mass Spectrometry for the Simultaneous Analyses of 35 Mycotoxins and Their Derivatives in Cereals - Dan-Bi Kim; Miso Nam; Yong-Suk Kim; Min-Sun Kim (Foods)
Mycotoxins occur singly or as co-contaminants and are primarily present in carbohydrate-rich foods such as cereals and cereal-based products. To effectively monitor mycotoxin co-contamination in cereals and cereal-based products, the simultaneous analysis of mycotoxins and their derivatives is required. Therefore, we coupled cleanup with LC-MS/MS for the rapid and robust quantitation of 35 analytes in wheat samples, including ergot alkaloids (EAs), which are rarely included in such analyses. To investigate the effects of different mycotoxin types on adsorbents, various dispersive solid-phase extraction sorbents were evaluated; a C18 end-capped sorbent exhibited the most effective cleanup performance. The method was validated by analyzing samples fortified with the mycotoxins at three concentration levels. The results exhibited high linearity, high recoveries, and repeatability. The methodology was applied for commercial cereal samples. The cereal samples were found to be 74% contaminated, and two samples measured levels of EAs at 609.63 μg/kg and 294.93 μg/kg, exceeding the limits defined by the EU for rye milling products. These findings highlight the validity of our novel method and the necessity of continuously monitoring mycotoxin levels in cereals to ensure food safety.